Recruitment of child soldiers by rebels in Afghanistan: the role of Pakistani madrasas - Qanet, Ghulam Mohammad; Eishan Jan, Mohammad Naqib (Serials Publications (P) Ltd., 2019)
This study investigates the link between religious schools, called madrassas, in Pakistan and recruitment and use of child soldiers in the long-lasting armed conflict in Afghanistan. A great deal of existing research on this and related topics has pointed to Pakistani madrassas as primary recruitment sites for the underage soldiers fighting in the armed conflict in Afghanistan, yet the precise circumstances on how the militancy entered the madrasa are insufficiently presented. The study examines the topic from the international law perspective as well as national legislations of Afghanistan and Pakistan. The bulk of the research relies on the use of doctrinal method. The relevant treaties, and the laws of Afghanistan and Pakistan are analysed. Additionally, the research uses qualitative textual analysis of relevant non-legal sources for the study. Research findings indicate that national laws of Afghanistan and Pakistan are congruent with international provisions on child soldiering. As a result, the study establishes that more underage combatants have been recruited from the Pakistani madrassas during the period of Soviet invasion of Afghanistan and the civil war that resulted in the Taliban assuming power in Afghanistan than it has been the case in the post 9/11 stage of armed conflict in Afghanistan.